Design of Pineapple Peeler Machine - Yuli Noersalim; Achwil Putra Munir; Ainun Rohana (Jurnal Rekayasa Pangan dan Pertanian, 2015)
At this time peeling pineapple fruit is known only through manual tools by kitchen knife. However, later on pineapple peeler has begun to be developed in the form of pineapple peeler manually press by using human operator. With the development of science and technology in this modern age, human  beings that have the potential to think will always develop and trying to create or make a new, more efficient and practical equipment that can help or even replacing human power with the agricultural machinery. Therefore through design in this research, the author tried to ease the peeling of pineapple skin by designing a pineapple peeler machine which had a larger capacity and without human power which be more effective and efficient in peeling pineapple. This principle of the pineapple peeler machine was worked that pineapples were embedded in the blade player who spins the fruit and withheld by the retaining lever and then the blades that have been mounted on a holder would come down to peel the fruit  that suited to its size. This machine can peel all kind of ripe pineapple fruit-size. The capacity of this pineapple peeler machine was 31,57 kg/hour. Keywords : blade, equipment design, pineapple peeler